Diagnoses the causes of cost deviation in Iraqi construction projects - Eman Mahde; Nidal A. Jasim (Diyala Journal of Engineering Sciences, 2021)
Root cause analysis techniques are an excellent choice for identifying the root causes of cost deviation in Iraqi construction projects. Many root cause analysis tools, such as the Fishbone diagram (FD), Pareto diagram (PD), and 5-Why analysis, have started to emerge from the literature as standard guidelines for identifying root causes. This study identified eighteen causes of cost deviation in construction projects, which they classified into three major groups (planning causes, designing causes, and execution causes). Pareto study indicates that twelve causes out of eighteen represent the most significant causes of cost deviation. After that, these eleven causes were filtered by 5-Why analysis, which concluded that insufficient project information and the implementation method is not appropriate with the project type are root causes for the planning group, while unclear owner requirements and changes in design are root causes for the designing causes group, Finally, changes in orders is a root cause for execution group.